Regional Income, Household Expenditure, Poverty, and Education Convergence Clubs at the District Level in Indonesia - Muhammad Zulfiqar Firdaus (Universitas Negeri Malang, 2023)
This article reinvestigates the regional convergence in GDP per capita, household expenditure per capita, poverty rate, and average years of schooling in Indonesia at the district level during 2000–2017 using the convergence club method. This article finds that regional inequality in Indonesia at the district level is characterized by two convergence clubs in GDP per capita, five convergence clubs in household expenditure per capita, six convergence clubs in poverty, and five convergence clubs in average years of schooling. This article also confirms the existence of spatial concentration among regions and a development gap between the west and east sides of Indonesia.